Cortes de plantas de mandioca na estação seca e seus efeitos na produção de fitomassa de parte aérea e de raízes. - Araújo, Cybelle Medeiros de (2011)
Aiming to evaluate the production of phytomass of the air parts and roots submitted to different cutting time, and its posterior use in animal feeding in drought critical periods, it has been used the cassava varieties commonly exploited in the region, being them: “ Olho de urubu”, “Branca”, “Baia preta”, and “Rosinha”. The test has been conducted at the Experimental Station of the State Company of Agricultural Research from Paraíba State, in Alagoinha city - PB, micro-region from Guarabira city, with 140 m height. The soil in the experimental area has been classified as CHROMIC LUVISOIL Palic abrupt. The experimental area was composed by three complete randomized blocks, in factorial scheme 4 x 4 (characterized by four cutting times and four varieties). The cutting times have been represented by: 1) cassava without cutting the air part (witness); 2) cassava submitted to cutting the air part in September; 3) cassava submitted to cutting the air part in October and 4) cassava submitted to cutting the air part in November. From the achieved results, it has been verified that the cuts which were performed in different months and the one which was performed in the end of the harvest did not affect the phytomass production of the air part, being all tropical varieties to produce roots and fodder. The treatments did not interfere in the roots production. The varieties “bravas” have been considered as the best producers, both in the production of fresh and dry phytomass of the air part, in the roots production and roots dry phytomass.